2021
DOI: 10.1021/acs.orglett.1c01814
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Spiro-γ-butyrolactone Core via Cascade Photochemical Reaction of 3-Hydroxypyran-4-one Derivatives

Abstract: We elaborate a novel one-step photochemical method for the synthesis of spiro-γ-butyrolactone derivatives from 3-hydroxypyran-4-ones. The suggested approach is based on a cascade process including initial photoinduced contraction of 4-pyranone ring followed by intramolecular cyclization leading to the final spiro system. A distinctive feature of the proposed method is intramolecular trapping of unstable α-hydroxydiketone intermediate formed in situ as a result of a photochemical reaction. The structures of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The starting pyrazoles 12 containing the 3-hydroxypyran-4-one fragment were obtained by a literature method [ 33 ]. The methoxy derivative 16 was synthesized by methylation of the corresponding pyrazole 12a according to the standard procedure [ 24 , 26 ] ( Scheme 2 ). Initially, based on the previously obtained results for terarylenes with an oxazolone bridge fragment, we chose pyrazole 16 containing a methoxy group in the allomaltol core as a model object for studying photochemical properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The starting pyrazoles 12 containing the 3-hydroxypyran-4-one fragment were obtained by a literature method [ 33 ]. The methoxy derivative 16 was synthesized by methylation of the corresponding pyrazole 12a according to the standard procedure [ 24 , 26 ] ( Scheme 2 ). Initially, based on the previously obtained results for terarylenes with an oxazolone bridge fragment, we chose pyrazole 16 containing a methoxy group in the allomaltol core as a model object for studying photochemical properties.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative approach for trapping of such unstable intermediates is the preliminary introduction of functional groups into the 3-hydroxypyran-4-one structure. In this case, the intermediate α-hydroxy-1,2-diketone is captured by intramolecular reaction with an active substituent in the side chain ( Scheme 1B ) [ 24 25 ]. Thus, the combination of ESIPT-induced photoreactions of 3-hydroxypyran-4-one derivatives and various trapping methods opens up significant synthetic possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of literature reports, the excited-state intramolecular proton transfer (ESIPT) plays a key role in phototransformations of the 3-hydroxypyran-4-one core. We supposed that alkylation of the hydroxyl group in an allomaltol moiety of compounds 12 will lead to blocking the ESIPT process and excluding the photoinduced contraction of the pyran-4-one ring.…”
Section: Resultsmentioning
confidence: 99%
“…Photoinduced reactions of heterocyclic compounds are an important part of organic chemistry. Among the wide variety of processes of this type, considerable attention is drawn to the phototransformations of compounds containing an allomaltol fragment [13–20] . In addition, note that the modification of allomaltol using classical synthetic methods opens up access to a wide range of products containing a 3‐hydroxypyran‐4‐one fragment [21–23] .…”
Section: Introductionmentioning
confidence: 99%
“…Further capture of the aforementioned labile intermediates allows the synthesis of diverse heterocyclic systems. It should be noted that such trapping can be carried out either under action of the additional reagents [13,14] or intramolecularly using functional groups of the side chain [15,17] (Scheme 1, A). Earlier we have shown that the ester and amide fragments can be used in this capacity.…”
Section: Introductionmentioning
confidence: 99%